PEMANFAATAN PASIR PANTAI SEPEMPANG DAN BATU PECAH ASAL RANAI SEBAGAI BAHAN PEMBUATAN BETON NORMAL - Siregar, Ahmad Husin; Satyarno, Satyarno; Tjokrodimuljo, Tjokrodimuljo (Civil Engineering Forum Teknik Sipil, 2008)
Dealing with development in many physical structure and infrastructure sectors, the use of concrete as building component is so wide. Natuna Regency area in manner concrete production always face difficulty in material, crushed aggregate and sand, because this material most of portion was still supplied from outside Natuna Regency that is Tanjung Pinang. In fact local material is quite enough, stone and sand, that wasn’t used optimally. However, the use of material need to be study, this why the research was performed. This study has objective to determine characteristic of nature Sepempang’s sand and Ranai’s crushed aggregate as normally concrete material. This research used material consist of Sepempang’s sand as material, Ranai’s crushed aggregate and Gresik’s Portland cement Type I. Mix design was fixed with water cement ratio (w/c) 0.4; 0.5; 0.6 with slump variable value 6±2 cm and 12±2 cm. Total variation is 6 pieces, each variation 9 pieces cylinder and 3 cube test material. Test result shows Sepempang’s sands have fine sand grading 3.07 fineness modulus (FM), SSD density 2.58; 1.49 of bulk density; 0.44% of clay and other fine material, 242.77 ppm (0.024277%) of salt content and 147.24 ppm (0.014724%) of chloride ion. Ratio fines aggregate-crushed aggregate to concrete mix with slump value 6±2 cm is 35%:65%, and for 12±2 cm slump value is 40%:60%. Ranai’s crushed aggregate has fineness modulus (FM) 7.13; 2.65 of SSD density, 1.52 of bulk density; 1.13% of absorption and 40.94 ppm (0.004094%) of chloride ion. Concrete with water cement ratio (w/c) 0.4 with cement content 475 kg/m3 and 550 kg/m3 respectively, have compressive strength 37.33 MPa and 36.20 MPa, for water cement ratio (w/c) 0.5 with cement content 380 kg/m3 and 450 kg/m3 respectively, have compressive strength 35.51 MPa and 31.68 MPa, and for water cement ratio (w/c) 0.6 with cement content 317 kg/m3 and 375 kg/m3 respectively have compressive strength 27.69 MPa and 26.26 MPa. The result of this research the Modulus of Elasticity of concrete formula E = 4328 f 'c . The ratio of concrete compressive strength 3, 7, and 28 days age was 68%, 87%, and 100%. Generally, the conclusion is Sepempang’s seashore sands and Ranai’s crushed aggregate appropriate as normal concrete material.